Implementasi Metode Simple Multi Attribute Rating Technique (SMART) Untuk Pengambilan Keputusan Pemilihan Obat Herbal - Petti Sijabat; Arjon Samuel Sitio (Jurnal Sains dan Teknologi, 2021)
All levels of society basically want to have a healthy and fresh body. Every activity or activity that ends with the goal of overcoming a fat body so that it is hoped that it will no longer be fat, is interpreted as an activity or diet activity. Overcoming a fat body into an ideal body is very difficult for consumers to do. Many consumers find an easy and fast alternative way to process their diet program. The search for herbal medicine to meet one's dietary needs requires a lot of effort and time, rather than finding chemical drugs that tend to be relatively easy, but have more dangerous properties than consuming herbal medicines, which tend to be very few side effects. For this reason, consumers are expected to consume herbal medicines that are much safer, rather than consuming chemical drugs that are harmful to the health of the body.This paper discusses ways to overcome problems in choosing herbal medicines for the right diet so that it can provide a positive response for every consumer in consuming herbal medicine to meet their dietary needs in their life. The Simple Multi-Attribute Rating Technique (SMART) method is a multi-attribute decision-making method. This multi-attribute decision-making technique is used to assist the process of selecting herbal medicines for the right diet so that the results given are more accurate